A national survey of clinical practice for the management of whiplash-associated disorders in UK emergency departments. Issue 9 (21st August 2009) - Lamb, S E; Williams, M A; Withers, E; Perry, J; Gates, S; Williamson, E; Underwood, M; Cooke, M
Abstract : Objective: To undertake a national survey to determine current practice for the management of whiplash injuries in UK emergency departments (ED). Methods: Postal questionnaire survey. 316 lead consultants from all UK ED with annual new attendances of over 50 000 people were asked to indicate the use of a range of treatments and the frequency with which these treatments were used. Samples of written advice were requested and content analysis was conducted and compared with survey responses. Results: The response rate was 79% (251/316). The intervention most frequently used was verbal advice to exercise, reported by 84% of respondents for most or all cases, and advice against the use of a collar (83%). Other treatments reported as being used frequently were written advice and anti-inflammatory medication. 106 consultants (42%) provided a sample of written materials. Reference to expected recovery and encouragement for early return to activities were included in less than 6%. Nearly 50% of written materials contained information on how to use a soft collar and 61% contained information on solicitors and pursuing a personal injury claim. There were important differences between reported verbal behaviours and written advice. Conclusion: Verbal advice is the primary method for managing whiplash injuries in ED and is usually supplemented by written advice. Within individual hospitals there is a lack of consistency between verbal and written advice. The promotion of personal injury claims is a common feature of written advice. Research is required to develop effective and consistent models of advice.